The Value-Added Tax : Its Causes and Consequences - Lockwood, Ben.; Keen, Michael (Washington, D.C. : International Monetary Fund, 2007)
Has the VAT proved, as its proponents claim, an especially effective form of taxation? To address this, this paper first shows that a tax innovation-such as the introduction of a VAT- reduces the marginal cost of public funds if and only if it also leads an optimizing government to increase the tax ratio. This leads to the estimation, on a large panel, of a system of equations describing the probability of VAT adoption and the revenue impact of the VAT. The sign of the revenue impact is generally ambiguous, but most countries that have adopted a VAT seem to have gained a more effective tax instrument in doing so.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet